Irinotecan for relapsed Wilms tumor in pediatric patients: SIOP experience and review of the literature—A report from the SIOP Renal Tumor Study Group. Issue 2 (27th October 2017) - Hol, Janna A.; van den Heuvel‐Eibrink, Marry M.; Graf, Norbert; Pritchard‐Jones, Kathy; Brok, Jesper; van Tinteren, Harm; Howell, Lisa; Verschuur, Arnauld; Bergeron, Christophe; Kager, Leo; Catania, Serena; Spreafico, Filippo; et al.
Abstract: While irinotecan has been studied in various pediatric solid tumors, its potential role in Wilms tumor (WT) is less clear. We evaluated response and outcome of irinotecan‐containing regimens in relapsed WT and compared our results to the available literature. Among 14 evaluable patients, one complete response (CR) and two partial responses (PRs) were observed in patients with initial intermediate‐risk (CR and PR) and blastemal‐type histologies (PR). Two patients were alive at last follow‐up showing no evidence of disease. Our results and the reviewed literature suggest some effectiveness of irinotecan in the setting of relapsed WT.